A Repositioning Strategy: A failure or a success story - Mikulandra Volić, Ivona; Relja, Ina; Brković, Mate (Oeconomica Jadertina, 2017)
The issue of disinvesting and the exiting of a company from a business regardless of their performance is of a critical importance for its further activities. The attention of researchers is more focused on the buyer’s side of the story than the seller since the acquisition implies a growth that is equated with success, and sales are usually perceived as a failure without noticing the potential positive consequences for the seller. Exiting the core business by implementing a repositioning strategy can bring a significant strategic change for the enterprise, as well as being a continuation for the enterprise as well as for the entrepreneur of the previous successful business. By presenting a case study this paper analyses the possible causes and questions the justification for the implementation of the repositioning strategy in three selected Croatian companies (Adris Group d.d., Lura Group d.o.o. and Jolly Jbs d.o.o.) that through the process of mergers and acquisitions appear in the role of sellers, and by doing that they exited their core business that helped them gain a high level of customer recognition and business reputation among competitors and associates. The analysis provides insight into a seldom-analyzed application of the repositioning strategy of Croatian companies and it contributes to a better understanding of disinvestment and the impact of the repositioning strategy on the company’s performance.